1998
DOI: 10.1136/bjo.82.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser iridotomy in pigment dispersion syndrome: an ultrasound biomicroscopic study

Abstract: Aims-Ultrasound biomicroscopy was used to study the shape of the iris and the iridolenticular contact in pigment dispersion syndrome (PDS) eyes, to compare them with matched normal eyes, and to assess the morphological eVects of laser iridotomy in PDS eyes. Methods-50 eyes of 50 patients suVering from PDS (group 1), and 15 normal eyes of 15 subjects matched for age and refraction (group 2), were studied by ultrasound biomicroscopy (UBM, Humphrey-Zeiss). Nd:YAG laser iridotomy was proposed to the 30 PDS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…22(p599) Concurrent abnormalities of the iris, as well as comorbidities and genetic factors, must play a role in facilitating the loss of pigment from the posterior iris surface. 5,23 In our study, 58 of 117 PDS eyes had a positive phenylephrine test result. When left untreated, more than 60% of these eyes showed an increase in IOP of 5 mm Hg or higher during the 10-year follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…22(p599) Concurrent abnormalities of the iris, as well as comorbidities and genetic factors, must play a role in facilitating the loss of pigment from the posterior iris surface. 5,23 In our study, 58 of 117 PDS eyes had a positive phenylephrine test result. When left untreated, more than 60% of these eyes showed an increase in IOP of 5 mm Hg or higher during the 10-year follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies have used ultrasound biomicroscopy to investigate the effect of Nd:YAG laser iridotomy on the configuration of the anterior segment in PDS and have found that iridotomy decreases iris-lens contact [3]; restores normal iris shape [5]; increases the depth of the posterior chamber [14]; prevents iris concavity with accommodation [16]; andcauses iris configuration to remain plain after exercise [11]. Furthermore, a traumatic defect of the peripheral iris appears to protect against development of PDS and PG [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, laser iridotomy may have application for some patients in the treatment of classic PDS. [42][43][44][45] Better classification of pigment dispersal syndromes may assist in those subgroups who would most benefit from such procedures.…”
Section: Discussionmentioning
confidence: 98%